Clinical outcomes of a digital musculoskeletal women’s pelvic health program: an observational, longitudinal study with comparison group - Mindy Hong; Rachel Foster Kirk; Bijal Toprani; Cynthia Castro Sweet; Clare Pan; Jeffrey Krauss; Tamara Grisales (BMC Women's Health)
Abstract Background Chronic pelvic pain is a common yet undertreated condition that significantly impacts quality of life for women worldwide. Digital exercise therapy designed to target pelvic pain can improve symptomology while reducing time and cost-related barriers to in-person clinical care. Methods This longitudinal, observational study of a digital women’s pelvic health program examined pelvic pain, anxiety, and depression at 4 and 12 weeks in female adults experiencing chronic pelvic pain. Intervention participants received a digital pelvic health program including personalized exercise therapy sessions, health education articles, and health coaching. A comparison group of nonparticipants received a series of education articles related to pelvic health. Data were collected at baseline, 4 and 12 weeks. Unadjusted and adjusted linear mixed effects models were conducted to model changes in clinical outcomes over time. Results A total of 797 participants (intervention: 495, nonparticipants: 302) were included in the sample. Baseline mean (SD) age was 41.5 (11.7) years and mean pain was 45.7 (18.5) out of 100. Compared to baseline, the intervention group showed significantly more pain improvement at 4 and 12 weeks versus nonparticipants after adjusting for baseline factors. The intervention group’s pain scores decreased by 44.5% at 4 weeks and 53.6% at 12 weeks. The intervention group’s adjusted pain scores decreased from 42.0 (95% CI: [39.4, 44.7]) at baseline to 23.3 (95% CI: [20.5, 26.2]) at 4 weeks to 19.5 (95% CI: [16.7, 22.4]) at 12 weeks. In contrast, nonparticipants’ pain scores decreased by 21.6% at 4 weeks and 32.7% at 12 weeks. Nonparticipants’ adjusted pain scores decreased from 42.1 (95% CI: [38.4, 45.9]) at baseline to 33.0 (95% CI: [29.2, 36.8]) at 4 weeks to 28.3 (95% CI: [24.5, 32.2]) at 12 weeks. After adjustments, the probability of the intervention group screening for moderate or severe depression was significantly lower by 11.0% at 12 weeks versus nonparticipants. There were no significant differences in anxiety outcomes between groups at baseline, week 4, or week 12.  Conclusions A digital women’s pelvic health program may help reduce short-term pelvic pain and depression symptoms. Trial registration The WIRB-Copernicus Group Institutional Review Board (registration number IRB20234932) approved this study on November 6, 2023.